2021
DOI: 10.11606/s1518-8787.2021055003375
|View full text |Cite
|
Sign up to set email alerts
|

Breast imaging hindered during covid-19 pandemic, in Brazil

Abstract: OBJECTIVE: To report the decrease in breast imaging after covid-19 pandemic, obtaining the number of mammograms performed in 2019 and 2020. Additionally, to investigate if there was an increase in the proportion of women undergoing mammography for diagnostic purposes, with palpable lesions. METHOD: This is a cross-sectional study, based on the number of mammograms performed by the Brazilian public health services, provided by DATASUS, an open access database. Mammograms from private institutions were not inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 11 publications
0
32
0
10
Order By: Relevance
“…Table 3 compares the number of mammograms performed during the pandemic vs. the same time period before the pandemic. Reductions in screening mammography rates were reported in all studies and ranged from 53.8% to 22.2% among registry-based studies 20 , 35 , 44 and 80.0% to 9.8% among non-registry-based studies. 18 , 24 , 25 , 31 , 34 , 36 , 39 , 41 , 43 , 49 Figure 2 displays the results of the meta-analysis of mammographic screening rate ratios.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Table 3 compares the number of mammograms performed during the pandemic vs. the same time period before the pandemic. Reductions in screening mammography rates were reported in all studies and ranged from 53.8% to 22.2% among registry-based studies 20 , 35 , 44 and 80.0% to 9.8% among non-registry-based studies. 18 , 24 , 25 , 31 , 34 , 36 , 39 , 41 , 43 , 49 Figure 2 displays the results of the meta-analysis of mammographic screening rate ratios.…”
Section: Resultsmentioning
confidence: 85%
“…Therefore, 33 reports consisting of 31 studies formed the basis of this review. 18 50 A PRISMA flow diagram outlining the screening process is presented in Figure 1 . The list of excluded studies with reasons of exclusion is reported in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In diagnosis, it will lead to an upstaging of tumor worsening prognosis, reducing women's quality of life, demanding more resources to the health care system to treat more complex situations. 3,[10][11][12][13] This study aimed to evaluate the diagnostic profile of breast cancer cases during the COVID-19 pandemic in users of the public health system in a populous urban city in Brazil, compared with the same period of the previous year. Clinical and pathological characteristics were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, in the city of Fortaleza, the decrease of screening mammograms was up to 95% [ 10 ]. In a cross-sectional study of the Brazilian public health system, the decline in mammograms reached 42% all over the nation from 2019 to 2020 [ 11 ]. In the case of cervical cancer, a Californian study showed that during the pandemic, when the population was recommended to stay at home, cervical cancer screening rates decreased by 78% [ 12 ].…”
Section: Discussionmentioning
confidence: 99%